(untitled) (International Conference on Education, Psychology and Humanities, 2026)
In the context of globalization and rapid digital transformation, the modernization of the educational system imposes new requirements on contemporary pedagogical activity. In particular, improving the professional competence, scientific thinking, and methodological preparedness of future teachers has become one of the priority directions of modern educational policy. Today’s educational environment requires teachers not only to possess profound theoretical knowledge within their field but also to deeply understand professional pedagogical terminology, accurately interpret scientific concepts, and effectively apply them in pedagogical communication. The active use of such concepts as “competency-based approach,” “digital pedagogy,” “integrative education,” “interactive methods,” “creative thinking,” “artificial intelligence technologies,” and “adaptive learning” significantly increases the relevance of developing pedagogical terminological competence. The article analyzes the linguocognitive features of developing pedagogical terminological competence in future teachers and substantiates its role in shaping scientific-pedagogical thinking, professional communication, and methodological culture.